Experiences of healthcare for people living with multiple sclerosis and their healthcare professionals. (4th September 2021) - Price, Eluned; Lucas, Robyn; Lane, Jo
Abstract: Background: Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative condition of the central nervous system that commonly strikes in young adulthood and has no cure. Many people living with MS (PwMS) will have significant contact with a range of healthcare professionals (HCPs). To achieve optimal health outcomes in MS, it is important to understand factors that contribute to positive or negative healthcare experiences. Previous studies have shown that PwMS want clear communication and in‐depth relationships with their HCPs. However, many studies have lacked qualitative feedback from HCPs. Objective: This study aimed to investigate healthcare experiences of PwMS and HCPs and identify areas that are working well and areas that could be improved. Methods: Semistructured interviews with 15 PwMS and 11 HCPs (seven neurologists, four MS nurses) from across Australia were conducted. Interviews were transcribed verbatim and analysed thematically. Results: Both PwMS and HCPs valued clear communication, recognized uncertainties associated with MS and highlighted the importance of rapport. PwMS focused on decision‐making, understanding roles and expectations, self‐directed management and their needs for support. HCPs discussed issues related to medical management, providing hope and reassurance, barriers to healthcare and multidisciplinary care. Conclusion: Greater transparency and communication, particularly around the approach to care and the roles played by HCPs, is likely to enhance healthcare experiences and contribute to better health outcomes for PwMS. Public Contribution: PwMS and HCPs volunteered to be interviewed, and PwMS assisted with the development of interview content and structure.